Silencing the silencers : Chaucer’s satire of clerical authority in the Nun’s Priest’s Tale - Lai, Daniel (2013)
This essay is a reading of Chaucer’s Nun’s Priest’s Tale as an anti-clerical satire, following others in the Canterbury Tales like the Friar’s, Summoner’s, and Pardoner’s Tales. Through the Nun’s Priest and Chauntecleer, Chaucer completes his anti-clerical satire by obliquely portraying priestly and sexual abuses. Within the larger frame of the “interacting polarities” of experience and auctoritee, Chaucer subversively portrays the representational incongruities of anticlerical satire in an ironic, ostensibly sententious moral allegory, highlighting the “severe contradictions” between the Church’s proclaimed Christian “self-representations” and the practices of its human representatives. Through the undermining of authoritative literary forms, the use of fable, anti-feminism and individualist verisimilitude, Chaucer parodies the authoritative exegetical structures he attacks, to show the hypocritical, self-seeking excesses that result from the unchecked discursive power of contemporary structures of clerical and exegetical authority. In so doing, he constitutes a new, more egalitarian politics of reading.